Mercury geochemistry and microbial diversity in meromictic Glacier Lake, Jamesville, NY. Issue 2 (20th February 2020) - Yoshimura, Kristin M.; Todorova, Svetoslava; Biddle, Jennifer F.
Summary: Meromictic lakes are stratified lakes that typically stimulate phototrophic anoxic microbial metabolism, including the transformation of sulphur. Less studied are the transformations of mercury in these environments, and the microorganisms, which mediate these reactions. In order to further an understanding of redox species, mercury and microbial populations in meromictic lakes, we examined the geochemistry and microbiology of Glacier Lake in Jamesville, NY. We found an anoxic transition at a depth of 6 m, followed by active nitrate and sulphate utilization. A chlorophyll a maximum was located at 11 m, coinciding with peaks of several photoautotrophic microbial lineages and total mercury and methyl mercury. Via amplicon sequencing, the microbial population showed pronounced peaks of cyanobacteria at 10 m, Chlorobi at 12 m and Chloroflexi at 14 m. Sulphate‐reducing bacteria were also most abundant between 10 and 14 m depth. A functional gene indicating the potential for the production of methyl mercury, hgcA, was detected at several depths in the lake. Our work suggests that in addition to the sulphur cycle, the cycling of mercury may be indirectly coupled with phototrophic processes in Glacier Lake.